Isolated Simultaneous Bilateral Adie’s Pupil - Khan, Summaya; Khizer, Muhammad Azeem; Khurshied, Saleh (Pakistan Journal of Ophthalmology, 2020)
Adie’s pupil, an efferent pupillary defect is caused by injury to parasympathetic pupillomotor nerve supply to Iris sphincter muscle. More commonly seen in young adult females with up to 80% cases having unilateral involvement. According to literature, Adie’s Pupil may occur alone or as a part of a systemic condition or may be associated with a syndromic presentation. Bilateral Adie’s pupil in a female at initial presentation with mild visual symptoms and no syndromic association is sparsely reported in literature.